Searching for Efficient Output Characteristics of Railway Power Station - Žižlavský, Petr; Mlynařík, Ladislav (International Academy of Science, Engineering, and Technology (International ASET), 2024)
This paper aims on new power converter supply stations on railway for 25 kV 50 Hz. Control system through output characteristics is introduced. A new approach of searching effective output characteristics is created and discussed. This approach defines four criteria which evaluate effectivity of railway traction grid. There was created a mathematical model of railway grid to test this criteria. In the last part of the paper there are presented results of simulations, followed by composed output characteristics and their meaning.
Nastavování výstupních charakteristik železničních napájecích stanic
Keywords: Power Converter Supply Station; Railway Power Stations; Simulation of Traction Grid; měničová napájecí stanice; železniční napájecí stanice; simulace trakční sítě